Girish Karnad the Master of Tragic Climax (International Journal of Food and Nutritional Sciences, 2022)
This study focuses on the similarities observed in the climaxes of Girish Karnad’s plays. Girish Karnad has created a monarchy for himself in the field of Indian Drama. He has combined native and western methods in the right proportion to seek new theatrical tactics and has proved successful the same. One important reason for the success of Karnad’s plays could be considered as the climax of the plays. Surprisingly, most of his plays have a tragic climax. This study tends to focus on these climaxes and relate the similarities in Karnad’s climaxes.